Seletividade de Beauveria bassiana e Metarhizium anisopliae ao predador Doru luteipes (Scudder) (Dermaptera: Forficulidae) - Resende, Rafael Carvalho de (2022)
Doru luteipes (Scudder) (Dermaptera: Forficulidae) is a voracious predator that plays an important ecological role in the regulation of pest arthropods. With wide natural occurrence in neotropical farming systems, it has a nocturnal habit and during the day it seeks shelter in narrow, humid and dark places, such as the corn plant cartridge. In addition, they are omnivorous insects, with the ability to use complementary resources such as corn pollen and spores of phytopathogenic fungi, which corroborates their establishment in the field. Females of D. luteipes have the peculiar behavior of caring for the eggs, called maternal care, through which they guarantee survival, reproductive potential and, possibly, protect the offspring against the entry of pathogens and subsequent infection. In order to integrate more sustainable insect pest control strategies, the use of fungal-based microbiological products is increasingly frequent, with emphasis on Beauveria bassiana (Balsamo), Vuillemin (Hypocreales: Clavicipitaceae) and Metarhizium anisopliae (Metchnikoff) Sorokin (Hypocreales: Clavicipitaceae). In the field, such fungi may present direct or indirect interactions with this predator, but they have not yet been measured. Considering the joint action of macro and microbiological agents, we first evaluated if the isolates IBCB 66 (B. bassiana) and IBCB 425 (M. anisopliae) are pathogenic to the different stages of D. luteipes and, later, if the manipulation of the eggs, carried out by the females during maternal care, prevents or reduces microbial infection. For the pathogenicity test, we used topical and dry film exposure of insects and fungal suspensions at increasing concentrations from 104 to 108 conidia.mL-1. Our results indicated that these isolates, at the concentrations and exposure methods tested, are not pathogenic to D. luteipes and, therefore, are compatible for use together. Additionally, we manipulated the presence or absence of maternal care after total and partial exposure of eggs to the same isolates, at a concentration of 108 conidia.mL-1. Our results showed that maternal care exercised by females of D. luteipes reduces the effects of exposure of eggs to entomopathogenic fungal spores and ensures successful embryonic and offspring development.